Metode Weight Product Untuk Pemilihan Pestisida Yang Sesuai Dengan Jenis Hamanya - Lubis, Fitri Amelia Sari; Nurcahyo, Gunadi Widi; Sovia, Rini (Universitas Putra Indonesia YPTK Padang, 2024)
Technological developments are now growing rapidly in various fields, including the implementation of technology in everyday life, including the world of business and organizations. Digital technology includes information, computing, communications and connectivity, becoming a key factor for achieving sustainable competitive advantage in various industries. The use of technology also provides benefits such as sales monitoring, business recommendations and better decision making. Decision Support System (DSS) is a system that is deliberately created to assist certain parties in making decisions with quality and objective results, in an effective and efficient way of working, and does not depend solely on subjective decisions or based on wrong parameters. . The Weight Product (WP) method is one of the solution methods in Decision Support Systems. Choosing the best product is an important decision in various aspects of life, from purchasing consumer goods to choosing technology in business. UD. Anugrah Jaya Tani is one of the kiosks in Sayur Mahincat village, Kec. Barumun Selatan, Padang Lawas Regency, which operates in the agricultural sector and sells various types of pesticides, herbicides and fertilizers. Pesticides are chemical substances and other materials used to control various pests. For farmers, the types of pests are mites, pest plants, plant diseases caused by fungi (fungi), bacteria and viruses, nematodes (worms that damage roots), snails, mice, birds and other animals that are considered detrimental. This research aims to determine pesticides that are suitable for the type of pest on plants. The method used is a Decision Support System (DDS), namely Weight Product (WP). The data used is 10 data with 6 predetermined criteria. The results of this research are based on the final value obtained from each alternative, the pesticide with the highest value is considered the best alternative and the result is that Alternative A5 is the best pesticide with the highest value of 0.1396, namely Sidabas. This means that the pesticide is considered to best meet the specified criteria with the weight given.